2013
DOI: 10.1183/09031936.00165712
|View full text |Cite
|
Sign up to set email alerts
|

A new class of bronchodilator improves lung function in COPD: a trial with GSK961081

Abstract: GSK961081 is a bifunctional molecule demonstrating both muscarinic antagonist and β-agonist activities.This was a 4-week, multicentre, randomised, double-blind, double-dummy, placebo and salmeterol controlled parallel group study. Doses ranging across three twice-daily doses and three once-daily doses were assessed in moderate and severe chronic obstructive pulmonary disease (COPD) patients. Trough forced expiratory volume in 1 s (FEV1) at day 29 was the primary end-point. At days 1 and 28, 12-h FEV1 spirometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 19 publications
10
46
0
Order By: Relevance
“…It has also to be mentioned a possible novelty, at least under the molecular point of view, because this substance, GSK 961081, has a structure where at one extremity it is present an antimuscarinic part, while at the other extremity it exhibits a Beta2 stimulant action. So, the same molecule could exert a double and complimentary action [134]. Molecules like this could indicate a road to the future.…”
Section: Analysis Of Currently Available Inhalation Drugs In Copdmentioning
confidence: 99%
“…It has also to be mentioned a possible novelty, at least under the molecular point of view, because this substance, GSK 961081, has a structure where at one extremity it is present an antimuscarinic part, while at the other extremity it exhibits a Beta2 stimulant action. So, the same molecule could exert a double and complimentary action [134]. Molecules like this could indicate a road to the future.…”
Section: Analysis Of Currently Available Inhalation Drugs In Copdmentioning
confidence: 99%
“…However, what is not yet clear is the relative contribution of the two different pharmacological activities to the overall improvement in lung function observed, and indeed on which pharmacological action such drugs should be optimally dosed, as some examples of MABAs have different pharmacodynamic half-lives for their b 2 -agonist activity and the muscarinic receptor antagonist activity with the same molecule [24,25]. However, a recent clinical study has demonstrated that treatment with three separate doses of GSK 961081 (once-daily doses of 100 mg, 400 mg or 800 mg, or twice-daily doses of 100 mg, 200 mg or 400 mg) showed superior improvements in lung function in patients with COPD compared with a standard dose of salmeterol (50 mg twice daily), suggesting that the MABA provides a better treatment than monotherapy with a b 2 -agonist [26]. In fact, differences between GSK 961081 doses and salmeterol treatment ranged from 78 mL (100 mg once daily) to 200 mL (800 mg once daily), with statistically significant differences in favour of GSK 961081 for all doses tested, except 100 mg once daily [26].…”
Section: Bifunctional Bronchodilator Drugsmentioning
confidence: 99%
“…However, a recent clinical study has demonstrated that treatment with three separate doses of GSK 961081 (once-daily doses of 100 mg, 400 mg or 800 mg, or twice-daily doses of 100 mg, 200 mg or 400 mg) showed superior improvements in lung function in patients with COPD compared with a standard dose of salmeterol (50 mg twice daily), suggesting that the MABA provides a better treatment than monotherapy with a b 2 -agonist [26]. In fact, differences between GSK 961081 doses and salmeterol treatment ranged from 78 mL (100 mg once daily) to 200 mL (800 mg once daily), with statistically significant differences in favour of GSK 961081 for all doses tested, except 100 mg once daily [26]. To date, however, a similar trial has not yet been performed comparing a MABA with monotherapy with an antimuscarinic drug.…”
Section: Bifunctional Bronchodilator Drugsmentioning
confidence: 99%
“…This novel nebuliser system offers the benefits of a reduced administration time compared with the conventional nebuliser and a more portable size with minimal noise levels. In a Phase IIb, multicentre, DBPC, four-period, crossover study 140 moderate-to-severe COPD subjects were randomised to receive SUN-101 (placebo, 25 [20]. SUN-101 was well tolerated with no significant safety concerns.…”
Section: Anticholinergicsmentioning
confidence: 99%